"You Can't Go to the Park, You Can't Go Here, You Can't Go There": Exploring Parental Experiences of COVID-19 and Its Impact on Their Children's Movement Behaviours - Negin A. Riazi; Kelly Wunderlich; Madelaine Gierc; Mariana Brussoni; Sarah A. Moore; Mark S. Tremblay; Guy Faulkner (MDPI AG, 2021)
The COVID-19 outbreak and related public health guidelines have changed the daily lives of Canadians and restricted opportunities for healthy movement behaviours for children. The purpose of this study was to explore how parents experienced the pandemic-related restrictions and how they impacted their children's movement behaviours. Methods: Twenty-nine semi-structured one-on-one interviews were conducted (June-July 2020) with parents of children (5-11 years old) in Ontario and British Columbia. Interviews lasted between 24-104 min, were audio-recorded, transcribed verbatim, and thematically analyzed. Results: Findings emphasized various individual (e.g., motivation), interpersonal (e.g., parent work schedule), built (e.g., closure of parks) and natural environment (e.g., weather) factors related to children's movement behaviours. The findings highlighted the loss of structured activities and destinations for children's physical activity, and restricted opportunities for outdoor play exacerbated by shrinking childhood independent mobility. Conclusion: Families are adapting to many pandemic-related challenges including adhering to public health restrictions, parents juggling multiple roles, conducting work and school from home, as well as exacerbating factors like weather. It will be important to continue to encourage outdoor time, support policies and practice that facilitate independent mobility, and develop centralized resources that help families in the maintenance of healthy movement behaviours.